Floating and stilted structures as strategies in coastal climate adaptation: Local monsoon adaptation practices and implications for flood risk management - Stefan Huebner (Climate Risk Management, 2025)
The physical “advance” onto aquatic surfaces through the use of floating structures is a new climate adaptation strategy for coastal regions. Sea level rise concerns have prompted international organizations like the IPCC and the UN to explore this advance strategy. The effectiveness of these floating structures, including floating buildings, as an adaptation strategy depends on social acceptance. This study applies a comparative analysis of case studies, identified through a systematic review of qualitative historical and present data, to investigate local forms of adaptation knowledge. Using data regarding parts of Asia, Africa, and South America, conceptually connected by the global monsoon system’s local impacts, it analyzes how advances onto or above aquatic surfaces using vernacular designs have affected inhabitants’ adaptation to the aquatic environment. It argues that vernacular houseboats, floating structures, and stilted (pile-elevated above the surface) structures have historically been a common, though not always environmentally sustainable, adaptation practice. The case studies of vernacular design knowledge support the serious consideration of the advance strategy in transformative coastal climate adaptation. Based on the findings, the article further argues that while vernacular stilted structures offer advantages for living on aquatic surfaces, their technologically advanced counterparts are impractical compared to technologically advanced floating structures. Research on this topic addresses a gap in the literature, as it connects vernacular and advanced implementations of the advance strategy to the booming interdisciplinary field of coastal climate adaptation, vernacular adaptation knowledge, and new guidelines for sustainable, socially accepted urban development.